Functionalization of heterocyclic compounds using polyfunctional magnesium and zinc reagents - Knochel, Paul; Schade, Matthias A.; Bernhardt, Sebastian; Manolikakes, Georg; Metzger, Albrecht; Piller, Fabian M.; Rohbogner, Christoph J.; Mosrin, Marc (Beilstein Journal of Organic Chemistry, 2011)
In this review we summarize the most important procedures for the preparation of functionalized organzinc and organomagnesium reagents. In addition, new methods for the preparation of polyfunctional aryl- and heteroaryl zinc- and magnesium compounds, as well as new Pd-catalyzed cross-coupling reactions, are reported herein. Experimental details are given for the most important reactions in the of this article.
Keywords: cross-coupling; heterocycles; insertion; metalation; organomagnesium; organozinc

(untitled) - Knochel, P. (Sci. Synth., 2004)

(untitled) - Knochel, P.; Millot, N.; Rodriguez, A.; Tucker, C. E. (Org. React., 2001)

(untitled) - Knochel, P.; Almena Perea, J. J.; Jones, P. (Tetrahedron, 1998)

(untitled) - Majid, T. N.; Knochel, P. (Tetrahedron Lett., 1990)

(untitled) - Zhu, L.; Wehmeyer, R. M.; Rieke, R. D. (J. Org. Chem., 1991)

(untitled) - Krasovskiy, A.; Malakhov, V.; Gavryushin, A.; Knochel, P. (Angew. Chem., Int. Ed., 2006)

(untitled) - Knochel, P.; Yeh, M. C. P.; Berk, S. C.; Talbert, J. (J. Org. Chem., 1988)

(untitled) - Boudet, N.; Sase, S.; Sinha, P.; Liu, C.-Y.; Krasovskiy, A.; Knochel, P. (J. Am. Chem. Soc., 2007)

(untitled) - Piller, F. M.; Metzger, A.; Schade, M. A.; Haag, B. A.; Gavryushin, A.; Knochel, P. (Chem.–Eur. J., 2009)

(untitled) - Negishi, E.; Valente, L. F.; Kobayashi, M. (J. Am. Chem. Soc., 1980)

(untitled) - Negishi, E. (Acc. Chem. Res., 1982)

(untitled) - Negishi, E.; Bagheri, V.; Chatterjee, S.; Luo, F.-T.; Miller, J. A.; Stoll, A. T. (Tetrahedron Lett., 1983)

(untitled) - Metzger, A.; Schade, M. A.; Knochel, P. (Org. Lett., 2008)

(untitled) - Schade, M. A.; Metzger, A.; Hug, S.; Knochel, P. (Chem. Commun., 2008)

(untitled) - Charles, M. D.; Schultz, P.; Buchwald, S. L. (Org. Lett., 2005)

(untitled) - Anderson, K. W.; Tundel, R. E.; Ikawa, T.; Altman, R. A.; Buchwald, S. L. (Angew. Chem., Int. Ed., 2006)

(untitled) - Barder, T. E.; Buchwald, S. L. (Org. Lett., 2004)

(untitled) - Gavryushin, A.; Kofink, C.; Manolikakes, G.; Knochel, P. (Org. Lett., 2005)
For other Ni-catalyzed cross-couplings of zinc reagents.

(untitled) - Gavryushin, A.; Kofink, C.; Manolikakes, G.; Knochel, P. (Tetrahedron, 2006)

(untitled) - Rieke, R. D. (Science, 1989)

(untitled) - Rieke, R. D.; Hanson, M. V. (Tetrahedron, 1997)

(untitled) - Piller, F. M.; Appukkuttan, P.; Gavryushin, A.; Helm, M.; Knochel, P. (Angew. Chem., Int. Ed., 2008)

(untitled) - Kondo, Y.; Shilai, M.; Uchiyama, M.; Sakamoto, T. (J. Am. Chem. Soc., 1999)

(untitled) - Hlavinka, M. L.; Hagadorn, J. R. (Tetrahedron Lett., 2006)

(untitled) - Krasovskiy, A.; Krasovskaya, V.; Knochel, P. (Angew. Chem., Int. Ed., 2006)

(untitled) - Lin, W.; Baron, O.; Knochel, P. (Org. Lett., 2006)

(untitled) - Wunderlich, S. H.; Knochel, P. (Angew. Chem., Int. Ed., 2007)

(untitled) - Mulvey, R. E.; Mongin, F.; Uchiyama, M.; Kondo, Y. (Angew. Chem., Int. Ed., 2007)

(untitled) - Wunderlich, S.; Knochel, P. (Org. Lett., 2008)

(untitled) - Knochel, P.; Dohle, W.; Gommermann, N.; Kneisel, F. F.; Kopp, F.; Korn, T.; Sapountzis, I.; Vu, V. A. (Angew. Chem., Int. Ed., 2003)

(untitled) - Ila, H.; Baron, O.; Wagner, A. J.; Knochel, P. (Chem. Commun., 2006)

(untitled) - Ila, H.; Baron, O.; Wagner, A. J.; Knochel, P. (Chem. Lett., 2006)

(untitled) - Jensen, A. E.; Dohle, W.; Sapountzis, I.; Lindsay, D. M.; Vu, V. A.; Knochel, P. (Synthesis, 2002)

(untitled) - Krasovskiy, A.; Knochel, P. (Angew. Chem., Int. Ed., 2004)

(untitled) - Boudet, N.; Lachs, J. R.; Knochel, P. (Org. Lett., 2007)

(untitled) - Krasovskiy, A.; Straub, B. F.; Knochel, P. (Angew. Chem., Int. Ed., 2006)

(untitled) - Wang, X.-j.; Xu, Y.; Zhang, L.; Krishnamurthy, D.; Senanayake, C. H. (Org. Lett., 2006)

Handbook of Functionalized Organometallic - Knochel, P.; Krasovskiy, A.; Sapountzis, I. (Polyfunctional Magnesium Organometallics for Organic Synthesis, 2005)

(untitled) - Ren, H.; Krasovskiy, A.; Knochel, P. (Chem. Commun., 2005)

(untitled) - Liu, C.-Y.; Ren, H.; Knochel, P. (Org. Lett., 2006)

(untitled) - Liu, C.-Y.; Knochel, P. (J. Org. Chem., 2007)

(untitled) - del Amo, V.; Dubbaka, S. R.; Krasovskiy, A.; Knochel, P. (Angew. Chem., Int. Ed., 2006)

(untitled) - Boudet, N.; Dubbaka, S. R.; Knochel, P. (Org. Lett., 2008)

(untitled) - Yamada, S.; Gavryushin, A.; Knochel, P. (Angew. Chem., Int. Ed., 2010)
For selective fluorinations of Grignard-reagents.

(untitled) - Mosrin, M.; Knochel, P. (Org. Lett., 2008)

(untitled) - Stoll, A. H.; Knochel, P. (Org. Lett., 2008)

(untitled) - Koradin, C.; Dohle, W.; Rodriguez, A. L.; Schmid, B.; Knochel, P. (Tetrahedron, 2003)

(untitled) - Clososki, G. C.; Rohbogner, C. J.; Knochel, P. (Angew. Chem., Int. Ed., 2007)

Metal-Catalyzed Cross-Coupling Reactions - de Meijere, A.; Diederich, F. (Wiley-VCH, 2004)

Transition Metal Reagents and Catalysts: Innovations in Organic Synthesis - Tsuji, J. (John Wiley & Sons, 1995)

Transition Metals for Organic Synthesis - Beller, M.; Bolm, C. (Wiley-VCH, 1998)

(untitled) - Manolikakes, G.; Schade, M. A.; Muñoz Hernandez, C.; Mayr, H.; Knochel, P. (Org. Lett., 2008)

(untitled) - Manolikakes, G.; Muñoz Hernandez, C.; Schade, M. A.; Metzger, A.; Knochel, P. (J. Org. Chem., 2008)

(untitled) - Corriu, R. J. P.; Masse, J. P. (J. Chem. Soc., Chem. Commun., 1972)

(untitled) - Tamao, K.; Sumitani, K.; Kumada, M. (J. Am. Chem. Soc., 1972)

(untitled) - Manolikakes, G.; Knochel, P. (Angew. Chem., Int. Ed., 2009)

(untitled) - Kienle, M.; Knochel, P. (Org. Lett., 2010)
For an iPrI accelerated Negishi coupling.

(untitled) - Metzger, A.; Bernhardt, S.; Manolikakes, G.; Knochel, P. (Angew. Chem., Int. Ed., 2010)

(untitled) - Bernhardt, S.; Metzger, A.; Knochel, P. (Synthesis, 2010)